Pertumbuhan Ekonomi Dan Ketimpangan antar Kecamatan di Kabupaten Buleleng - Kurnia Sari, Puput Desi; Sribudhi, Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 3, Maret 2013 (pp. 119-172), 2013)
This study discusses the economic growth and inter-district disparities in Buleleng regency in 2007-2011. Purpose of this study was to (i) determine the pattern of economic growth per district in Buleleng (ii) knew inequality inter district in Buleleng regency (iii) test hypotheses Kuznets about U interved in Buleleng. Analytical techniques used are typologies Klassen, Williamson an person correlation indeks. Klassen typology results only divided into two quadrant. Williamson indeks calculation rate is quite small and of the analysis has been done  on the interved U Kuznets hypothesis doesn’t apply in the Buleleng regency during the observation period. This study is expected to be able to entar for the local government district of Buleleng.
Keywords: economic development , inter-district disparities , Buleleng regency